How the conditions of the cubic equation arising out of conormals of a parabola are arrived at.
Asked by | 17th Dec, 2008, 08:04: AM
this is a qubic equatiion. let the roots are m1,m2,m3
so sum of roots = m1+m2+m3 = - (coefficient of m2 ) / (coefficient of m3 )= 0
m1m2+m2m3+m1m3 = (coefficient of m ) / (coefficient of m3 ) = (2a-x1) / a
and m1m2m3 = - constant / (coefficient of m3 ) = -y1 / a
you have written x1 in place of a. so please check. it should be a .
Answered by | 17th Dec, 2008, 10:13: AM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number